Teknik Pemberian dan Dosis Paket Pemupukan Pada Tanamankelapa Sawit (Elaeis guineensis jacq) di Lahan Gambut rimbo Panjang Kabupaten Kampar - Fransisca Sugiarti; Armaini '; Sukemi Indra Saputra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to determine the effect of provision fertilizer treatment techniques, fertilizer doses and interactions, and also to determine the best treatment for the growth and production of oil palm plantations on peatlands in Rimbo Panjang. The method used was Completely Randomized Design (CRD) factorial, consisting of two factors, namely the first fertilizer application techniques with 3 levels i.e spreading systems, burying systems and striping system. Factor II, the use of fertilizers with the level 2 as recommended (Urea=1.00kg/tree, TSP=0.88 kg/tree, MOP=0.75 kg/tree) and ½ the recommended dose (Urea=0.50kg/tree, TSP=0.44 kg/tree, MOP=0.38 kg/tree ) with four replications, in order to obtain 24 experimental units, which is every experimental unit had 2 plant so that the total are 48 plants. Data were analyzed statistically by analysis of variance followed by a Duncan test New Multiple Range Test at 5% level. The parameters measured were plant height accretion, stem girth, number of leaf, number of flowers palm bunches, and the number of bunches. Treatment combination with spreading fertilizer application system with ½ doses showed the best results in the accretion of plant height parameters, number of flowers palm bunches, and the number of bunches.Keywords : Palm oil, fertilizer, doses